Handbook of PI and PID controller tuning rules - AIDAN, O'DWYER (World Scientific Publishing Co. Pte. Ltd, 2009)
The vast majority of automatic controllers used to compensate industrial processes are PI or PID type. This book comprehensively compiles, using a unified notation, tuning rules for these controllers proposed from 1935 to 2008. The tuning rules are carefully categorized and application information about each rule is given. The book discusses controller architecture and process modeling issues, as well as the performance and robustness of loops compensated with PI or PID controllers. This unique publication brings together in an easy-to-use format material previously published in a large number of papers and books.